2005
DOI: 10.1128/jb.187.14.4822-4829.2005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of theospCRegulatory Element Controlled by the RpoN-RpoS Regulatory Pathway inBorrelia burgdorferi

Abstract: Outer surface lipoprotein C (OspC) is a key virulence factor of Borrelia burgdorferi. ospC is differentially regulated during borrelial transmission from ticks to rodents, and such regulation is essential for maintaining the spirochete in its natural enzootic cycle. Recently, we showed that the expression of ospC in B. burgdorferi is governed by a novel alternative sigma factor regulatory network, the RpoN-RpoS pathway. However, the precise mechanism by which the RpoN-RpoS pathway controls ospC expression has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
120
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 64 publications
(107 reference statements)
7
120
0
Order By: Relevance
“…Recently, using microarray and transcriptional analysis, Caimano et al have shown that whereas flagellum biosynthetic genes are controlled by 70 both in vitro and in vivo, the methyl-accepting chemotaxis genes mcp1, mcp4, and mcp5 and the chemotaxis gene cheW2 are upregulated by S (RpoS) (11) during growth in vivo. For B. burgdorferi, evidence suggests that S is directly controlled by 54 (61,66). 54 directly participates in the transcription of motility gene expression in other bacteria, such as Caulobacter crescentus, Vibrio species, Pseudomonas aeruginosa, and Helicobacter species (4,16,44,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using microarray and transcriptional analysis, Caimano et al have shown that whereas flagellum biosynthetic genes are controlled by 70 both in vitro and in vivo, the methyl-accepting chemotaxis genes mcp1, mcp4, and mcp5 and the chemotaxis gene cheW2 are upregulated by S (RpoS) (11) during growth in vivo. For B. burgdorferi, evidence suggests that S is directly controlled by 54 (61,66). 54 directly participates in the transcription of motility gene expression in other bacteria, such as Caulobacter crescentus, Vibrio species, Pseudomonas aeruginosa, and Helicobacter species (4,16,44,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all of the motility promoters identified so far are 70 -like (19,22,38). However, discrimination between S and 70 promoters in B. burgdorferi based on promoter consensus sequences is problematic (11,66). Recently, using microarray and transcriptional analysis, Caimano et al have shown that whereas flagellum biosynthetic genes are controlled by 70 both in vitro and in vivo, the methyl-accepting chemotaxis genes mcp1, mcp4, and mcp5 and the chemotaxis gene cheW2 are upregulated by S (RpoS) (11) during growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…pJD55 is a derivative of pJD44 in which the aph[39]-IIIa marker is replaced with PflgB-Kan of pBSV2 (Stewart et al, 2001). BbJSB18-B2 was transformed with the resulting construct, designated pJSB208B, as described previously by Yang et al (2005), and transformants were selected using kanamycin at a concentration of 160 mg ml 21 . Clones were confirmed by plasmid recovery, as described by Blevins et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by removing the 4.2 kb region from pXY240 by digestion with KpnI and XbaI and ligating it into pJD44 digested with the same enzymes. The resulting construct, designated pJSB259, was transformed into BbJSB19-A7B, as described previously (Yang et al, 2005).…”
mentioning
confidence: 99%
“…1B). The intergenic region between guaA and ospC, which includes the ospC promoter and regulatory operator sequences up to the ospC start codon (12,20,21,(37)(38)(39), was amplified from B. burgdorferi genomic DNA with primers 13 and 14 (Table 2), cloned into pCR2.1, sequenced, and digested with BamHI and XhoI for ligation into pBH-lacZBb, creating pBHospCp-lacZBb. Constructs were transformed into electrocompetent B. burgdorferi (27) and ⌬lac E. coli cells.…”
Section: Methodsmentioning
confidence: 99%